Analisis Implementasi Pengobatan Dan Pencegahan Dalam Pengendalian Hipertensi Di Apotek Peunawa Rahmat 2024 - Perry Boy Chandra Siahaan; Linda Mawati Harefa; Kiswanto Kiswanto; Maiza Duana; Onetusfifsi Putra (PT.Mantaya Idea Batara, 2025)
Non-communicable diseases are currently a serious problem, one of which is hypertension. The global prevalence of hypertension is 22% of the world's total population and the total number of hypertensive patients at the peunawa rahmat pharmacy and high blood pressure is a non-communicable disease that can occur and cause chronic disease. The main problem in hypertension is that it causes stroke. The aim of this research is to find out about patient knowledge in controlling hypertension through the role of hypertension control education. Method: research was qualitative with a design using questionnaires, observations, interviews, conducted from November and early December 2024. The key informant was a specialist doctor.internal Medicine and patient support informants. Results: This study shows that hypertension control in patients has been given good treatment. It was found that patients at the peunawa rahmat pharmacy when they consulted a specialist in internal medicine and hypertension began to improve from before. Conclusion: research provides education about a healthy lifestyle which is very important in controlling hypertension.